2016
DOI: 10.1166/jnn.2016.12431
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin-Releasing Hormone Loaded and Chitosan Engineered Polymeric Nanoparticles: Towards Effective Delivery of Neuropeptides

Abstract: Thyrotropin-Releasing Hormone (TRH), a tripeptide amide with molecular formula L-pGlu-L-His-L- Pro-NH2, is used in the treatment of brain/spinal injury and certain central nervous system (CNS) disorders, including schizophrenia, Alzheimer's disease, epilepsy, depression, shock and ischemia due to its profound effects on the CNS. However, TRH's therapeutic activity is severely hampered because of instability and hydrophilicity owing to its peptidic nature which results into ineffective penetration into the bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
1
1
0
1
Order By: Relevance
“…Due to the resistance forces between hydrophilic peptide and hydrophobic PLGA molecules, the diffusion of CGRP was very fast when contacted with the water phase which may result in the relatively lower loading efficiency of the peptide comparing to the double emulsion method [40][41][42]. However, the final loading efficiency, in this study, was comparable to other studies using the nanoprecipitation strategy with loading efficiencies ranging from 0.2% to 0.5% [43][44][45][46]. The PEG with hydrophilicity may retard the diffusion of the peptide which may lead to the higher loading efficiency comparing to the PLGA without modification.…”
Section: Fabrication and Characterization Of Nanoparticlessupporting
confidence: 59%
“…Due to the resistance forces between hydrophilic peptide and hydrophobic PLGA molecules, the diffusion of CGRP was very fast when contacted with the water phase which may result in the relatively lower loading efficiency of the peptide comparing to the double emulsion method [40][41][42]. However, the final loading efficiency, in this study, was comparable to other studies using the nanoprecipitation strategy with loading efficiencies ranging from 0.2% to 0.5% [43][44][45][46]. The PEG with hydrophilicity may retard the diffusion of the peptide which may lead to the higher loading efficiency comparing to the PLGA without modification.…”
Section: Fabrication and Characterization Of Nanoparticlessupporting
confidence: 59%
“…In the treatment of AD, soluble CTS nanoparticles were also found to safely and efficiently deliver piperine to targeted sites and multiply, which can reduce the oral dose by 20 times [ 99 ]. In this paper, Kaur et al [ 100 ] reported that the synthesis and stability studies of novel CTS engineered thyrotropin-releasing hormone encapsulation poly (lactide- co -glycolide) showed the potential membrane penetrating and effective delivery of neuropeptides, which were used in the treatment of brain/spinal injury and certain CNS disorders, including schizophrenia, AD, depression, etc. Rosmarinic acid-loaded polyacrylamide-chitosan-poly (lactide- co -glycolide) nanoparticles were grafted with cross-reacting material 197 and apolipoprotein E to pass across the BBB and rescuing neurodegeneration.…”
Section: Biological Activity Of Cts and Cos And Its Derivatives Inmentioning
confidence: 99%
“…Todas as imagens, tanto as topográficas quanto as de contraste de fase, foram fornecidas simultaneamente pelo equipamento durante a varredura de cada área. A técnica utilizada para a caracterização das partículas foi o espalhamento de luz dinâmico (DLS), que é amplamente utilizada para a avaliação físico-química de partículas, sendo relatada em diversos trabalhos envolvendo carreadores lipídicos (Marcato, 2009;Svilenov;Tzachev, 2014; Geszke-Moritz; Moritz, 2016) e poliméricos (Kaur et al, 2016). Dentre as vantagens da técnica de DLS estão a praticidade, facilidade de operação e velocidade na aquisição dos dados (Bohren;Huffman, 1983), vantagens estas que contribuíram para a escolha desta técnica para a etapa de caracterização de tamanho, índice de polidispersão e potencial zeta das partículas.…”
Section: Shimadzu Corporation Jpn) Na Faculdade De Filosofia Ciênciunclassified